The impact of various suture materials on experimental colorectal carcinogenesis - (:unkn) unknown (SPRINGER-VERLAG, 2001)
Local tumor recurrence following restorative surgery for colorectal cancer may occasionally result from the promotion of a neoplastic lesion in a zone of proliferative instability adjacent to the anastomosis. This study was designed to determine the influence of various suture materials on experimental colorectal carcinogenesis. A total of 72 rats were divided into six groups, four of which were subjected to colotomy and repair using catgut, silk, polyglactin (PG), or stainless steel. The fifth group was given a sham procedure and the sixth group served as a control. Methylnitrosourea was administered rectally to all the animals, at a dose of 4 mg/kg/week for 20 weeks. The mean number of tumors per rat was significantly higher in the PG group than in the other groups. The mean tumor size was found to be significantly larger in each of the suture material groups than in the sham group. A tendency for tumor occurrence to develop at the anastomosis rather than at the other colon sites was seen in the PG group. These results indicate that PG has an adverse effect on local tumor occurrence in experimental colorectal carcinogenesis.
Keywords: local recurrence; colorectal cancer; suture material; BIOFRAGMENTABLE ANASTOMOSIS RING; COMPRESSION ANASTOMOSIS; COLONIC ANASTOMOSES; BOWEL ANASTOMOSIS; PROGNOSTIC FACTORS; BLOOD-TRANSFUSION; TUMOR-FORMATION; TREATED RATS; CANCER; RECURRENCE